2021
DOI: 10.1093/police/paab065
|View full text |Cite
|
Sign up to set email alerts
|

Operational stress of police officers: A cross-sectional study in three countries with centralized, hierarchical organization

Abstract: Law enforcement is a stressful occupation with both work-related and social-related stressors. Too much stress can negatively affect behaviours, mental states, and job performance. Centralized police organizations limit officers’ individual autonomy, likely increasing stress. This study examined differences in occupational stress in two different European countries and one Middle East country. Participants were 351 male police officers from Serbia (n = 130, age 36 ± 8 years), Russia (n = 121, age 22 ± 4 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Exploratory and confirmatory factor analysis showed that the PSQ-op and PSQ-org are valid constructs, providing the evidence for both internal and external validity. Recent research on occupational stress from three different countries used principal component analysis to define the operational stress structure of police officers [5]. Authors found that operational stressors grouped into more work-related and social-related stressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploratory and confirmatory factor analysis showed that the PSQ-op and PSQ-org are valid constructs, providing the evidence for both internal and external validity. Recent research on occupational stress from three different countries used principal component analysis to define the operational stress structure of police officers [5]. Authors found that operational stressors grouped into more work-related and social-related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Operational content of police work includes, but is not limited to, work schedules, shift work, long work hours, court work and dangers to physical and psychological health; while the organizational environment refers to human elements that contribute to stress, such as bureaucracy and interpersonal interactions at work [4]. Furthermore, social-related stressor such as the difficulty of finding friends outside the job, not having time to spend with friends and family, and uploading "higher" picture in public play significant role in occupational stress of police officers [5]. Therefore, sources of stress in policing jobs are layered and interrelated so officers are often experiencing stress while at work but also while off-duty [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Law enforcement officials face scrutiny from the public because of their prominent cultural and societal roles in maintaining order and protecting residents through law enforcement. This highly visible dynamic obscures the origins of operational strain (Kukić et al, 2022). According to a survey of law enforcement professionals, the three most stressful aspects of the job are: (1) being held accountable for an officer-involved shooting, (2) witnessing the loss of a comrade in the line of duty, and (3) surviving a physical attack (Violanti et al, 2009).…”
Section: Operational Stress At Police Workmentioning
confidence: 99%
“…Even with the widespread interest in understanding antecedents of CWB, certain predictors have been focused on to a lesser extent. In the current research, I build on these previous contributions and extended prior findings to explore CWB as an outcome of social rank in an organization often characterized by power, rank, and hierarchy (i.e., a police organization; Drummond-Smith, 2018;Kukić et al, 2021). Utilizing the theoretical foundations of social dominance theory (Sidanius & Pratto, 1999), and dual strategies theory (Maner & Case, 2016), I argue that an important antecedent to CWB is employee traits characterized by an inclination to engage in actions that promote social rank.…”
Section: Counterproductive Work Behaviourmentioning
confidence: 94%